Gendered transformative initiatives in South Asia - Bhatia, Reema (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This volume discusses gendered transformative initiatives in South Asian feminism, discussing gender norms, labour and market participation by women, along with family planning, reproductive rights and initiatives for the social and financial empowerment of women in South Asia. Gender is a part of our everyday lived reality. It has been one of the key structuring principles of social interaction across societies. The context may be specific to a society, but it is also universal since it intertwines with everyone's lives. This book uses a bricoleur approach to understanding gender as a lived experience. These explorations examine the ways in which gendered identity is negotiated and lived. The volume uses a multi-methodological and multidisciplinary approach to discuss issues around conflict, work, queer identities, intersectionality and single women across Pakistan, Sri Lanka and Bangladesh. Part of the Social Movements and Transformative Dissent series, this volume will be of interest to students and researchers of gender studies, women's studies, sociology, economics, development studies, political science, cultural studies and South Asian studies"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Feminism -- South Asia; Women -- Civil rights -- South Asia; Women -- South Asia -- Social conditions; Womens Studies